Evaluation of heat-accumulating properties of organic acids and their composites with REE - Amerkhanova, Sh.K.; Alexandrov, V.D. (Изд-во КарГУ, 2014)
Sorption of collectors — dibuthyldithiophosphate of ammonium and sodium on samples of polymetallic ores was investigated. Values adsorption equilibrium was determined. The sorption curve of selective collector (dibuthyldithiophosphate sodium) was obtained. Also in the paper the comparative analysis of the flotation properties of dibuthyldithiophosphate ammonium and sodium respect to polymetallic ore of deposit «Nurkazgan» is given. A high selectivity of dibuthyldithiophosphate solution was established that enabled the development of flotation circuit.
Keywords: flotation; collectors; dibuthyldithiophosphate ammonium and sodium; polymetallic ore; metals; sorption; sorption capacity; selectivity